Employability Skills and Self-Efficacy Among Students at Biliran Province State University - Pabilando, Reymark S.; Sabonsolin, Ruth T. (Interdisciplinary Social Studies, 2023)
Background: Employability skills and self-efficacy among students in the university can be improved by providing them with the necessary resources and support. This includes providing students with access to career and employability services, such as career counseling, job search assistance, and resume writing services. Aim: This study was designed to investigate the employability skills and self-efficacy of students at Biliran Province State University. Method: The study used a survey questionnaire to collect data from a sample of 100 students from different colleges within the University. Findings: Results revealed that the students had low to moderate employability skills and self-efficacy. The results also showed that there were significant differences in employability skills and self-efficacy among students in different colleges at the University. The discussion of the results highlighted the importance of developing interventions to improve the employability skills and self-efficacy of students. The study concluded that the employability skills and self-efficacy of students at Biliran Province State University needed to be improved. Recommendations included providing training and workshops to help students develop their employability skills and self-efficacy.